Tamsulosin versus Alfuzosin as medical therapy for ureteric stones - Piya, B; Singh, SK; Gurung, R (Journal of Society of Surgeons of Nepal, 2016)
Objectives: To evaluate and compare the efficacy of tamsulosin and alfuzosin as medical therapy in ureteric stones. Patients and Methods: A total of 87 patients with ureteral stones of size ≤10 mm were randomly divided into 3 groups. Group I patients (n-30) received 0.4 mg of tamsulosin daily, group II patients (n-29) received 10 mg of alfuzosin daily and group III patients (n-28) received no alpha blockers. All patients were given analgesia when needed. Follow up was done in weekly basis for 4 weeks. Results: The mean stone size (5.33±1.58, 5.79±1.84, 5.67±1.64) and age (29.1±6.3, 30.31±7.22, 29.4±7.63) were comparable in each groups. The stone expulsion rate was 83.3%, 79.3% and 50% in group I, II and III respectively. The drugs related side effects reported by patients were mild and transient. Conclusion: The use of tamsulosin and alfuzosin for the medical treatment of ureteric stones proved to be safe and effective and neither did have any significant benefits over the other